Anomalous Ferromagnetism of quasiparticle doped holes in cuprate heterostructures revealed using resonant soft X-ray magnetic scattering - B. L. Ong; K. Jayaraman; C. Diao; T. J. Whitcher; A. Jain; H. Hung; M. B. H. Breese; E. S. Tok; A. Rusydi (Nature Communications, 2022)
Long-range magnetic order of quasiparticle doped holes is important for understanding the physics of cuprate superconductors, albeit difficult to probe in experiments. Ong et al. observe ferromagnetism of quasiparticle doped holes in a cuprate heterostructure and discuss implications for cuprates in the ground state.